Hegel's Historical Denialism and Epistemic Eclipse in African Philosophy. - (:unkn) unknown (My University, 2023)
African philosophy remains bedeviled by relics of Hegel’s racist chants against the rationality of Africans, and this situation deserves revisitation and reevaluation for reconstructive purposes. In this paper, I implicate Hegel’s concatenations as necessitating the reactive fervour within which a significant portion of the themes, thesis, and content of African philosophy is locked. This influence, which partially eclipses African philosophy, I term historical denialism. In an attempt to repudiate Hegel’s constructs, some philosophers in Africa seem ideologically contrived into developing or discovering an authentic philosophy for Africans, and in the process, advocate cultural essentialism as determinants of philosophy—at least logically. Averring that philosophy is not the sole representation of thought, I proceed by exploring other trajectories which could have informed a non-reactive African philosophy, while logically linking Hegel’s denialism to subtle silencing of his idealism within philosophical discourses in Africa. This subtle silencing, which shortchanges pedagogy of philosophy on the continent, forms the other half of the eclipse in philosophy in Africa. I conclude the discussion by asserting that while it may be imperative to exorcise Hegelian ghost in African philosophy, to use Olufemi Taiwo’s coinage, essentialising African philosophy would either further enmesh the field in a reactive predisposition, or limit its reflective and multifarious possibilities.
Keywords: African Research